Methodological Aspects of Teaching Effectiveness Evaluation - Ljubotina, Damir (2007)
The University of Zagreb evaluates teaching effectiveness thorough the quality assurance system. The paper discusses different quality indicators of teaching, their correlation, and their stability in time. (Empirical) analyses show that the student assessment is affected by a series of indicators like regular course attendance, student interest in course content, the size of student groups, student general study results, student expectations etc. Accurate results interpretation requires appropriate methodology, and combining different information on teaching effectiveness.
Projekt MZOS
ENG